Physical and photocatalytic properties of Nd codoped (Ag, Cu)TiO2 thin films. (3rd June 2021) - Mustafa, A.; Bououdina, M.; Al-Najar, B.; Souier, T.; Bensouici, F.; Belache, B.
ABSTRACT: Transparent co-doped TiO2 thin films have been fabricated by sol-gel dip-coating. The doping is achieved using low concentrations of neodymium (Nd), silver (Ag), and copper (Cu). A significant effect of doping is noticed on the morphology and optical properties of thin films. XRD analysis confirms the formation of a pure anatase phase with a deterioration of the crystallinity upon doping. The co-doped TiO2 thin films present larger crystallite size compared to other films. The surface roughness revealed by AFM increases from 0.9 nm for pure TiO2 up to 5 nm for doped thin films. UV-vis spectroscopy shows that the bandgap energy slightly decreased for co-doped Ag-Nd/TiO2 and Cu-Nd/TiO2 . Photocatalytic degradation of MB significantly decreases upon doping. A mechanism based on combined effects of doping, annealing and nature of substrate is proposed to explain the photodegradation behaviour. GRAPHICAL ABSTRACT: